Effect of fertilization on expression of bioactive carotenoid and chlorophyll pigments in clinacanthus nutans lindau for potential use as functional natural colourants - Zuhaili Yusof,; Noor Zalina Mahmood,; Rashidi Othman,; Jamilah Syafawati Yaacob, (Universiti Kebangsaan Malaysia, 2023)
This research aimed to investigate the different effects of fertilization (through the use of vermicompost and chemical fertilizer) on carotenoid composition as well as the chlorophyll content in Clinacanthus nutans Lindau. A field study employing a Randomized Complete Block Design (RCBD) was conducted on four treatment groups; control plants that were not supplied with any fertilizer (NF), plants supplemented with NPK chemical fertilizer (FC), plants supplemented with vermicompost (FV), and plants supplied with the mixture of chemical fertilizer and vermicompost (FM). Vermicompost application was shown to have insignificant effects on the expression of chlorophyll and carotenoid in C. nutans as compared to chemical fertilizer. However, the supplementation of vermicompost (FV and FM) produced plants with greater stability of compounds during storage, in contrast to NF and FC. The major carotenoids in C. nutans methanolic extracts supplied with vermicompost and organic fertilizers were identified as violaxanthin, lutein, α-Carotene and β-Carotene, while control plants lacked in α-Carotene and β-Carotene. This analysis provides a better insight into the application of vermicompost as an alternative source of growth supplements for the sustainable production of pigments which can act as a functional natural colourant and deliver great medicinal benefits to humans.